DESIGN CONSIDERATIONS IN THE FORMING OF AUTOMOBILE PARTS - ADEGBUYI, Patrick.Adebisi. Olusegun (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
Manufacturing is the main stay of any Nations economy, and the processof manufacturing starts with the production of machine components whichis made possible through putting ideas into design and a method ofmanufacture is determined. This work presents the design of a machine forforming the Back- Plate of a brake pad through stamping and punching.The tools used are called dies and are made having the specific shape thatneeds to be formed.